2005
DOI: 10.1016/j.febslet.2005.08.089
|View full text |Cite
|
Sign up to set email alerts
|

Compact oleic acid in HAMLET

Abstract: HAMLET (human alpha-lactalbumin made lethal to tumor cells) is a complex between a-lactalbumin and oleic acid that induces apoptosis in tumor cells, but not in healthy cells. Heteronuclear nuclear magnetic resonance (NMR) spectroscopy was used to determine the structure of 13 C-oleic acid in HAM-LET, and to study the 15 N-labeled protein. Nuclear Overhauser enhancement spectroscopy shows that the two ends of the fatty acid are in close proximity and close to the double bond, indicating that the oleic acid is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…56 Furthermore, Fast et al have indicated that oleic acid present in the monomeric population is bound to HAMLET in a compact conformation. 57 Combining the results mentioned above with those from our conductometry experiments (data not shown), we conclude that the state of oleic acid at pH 4.0-4.5 is a mixture containing monomeric oleic acid and oil but not micelles. We thus suggest that the inhibition of amyloid formation of apo-BLA by oleic acid at pH 4.0-4.5 is not due to detergent effects but results from the fact that monomeric oleic acid specifically induces the intermediate of apo-BLA at pH 4.0-4.5 to form insoluble amorphous aggregates.…”
Section: Discussionsupporting
confidence: 58%
“…56 Furthermore, Fast et al have indicated that oleic acid present in the monomeric population is bound to HAMLET in a compact conformation. 57 Combining the results mentioned above with those from our conductometry experiments (data not shown), we conclude that the state of oleic acid at pH 4.0-4.5 is a mixture containing monomeric oleic acid and oil but not micelles. We thus suggest that the inhibition of amyloid formation of apo-BLA by oleic acid at pH 4.0-4.5 is not due to detergent effects but results from the fact that monomeric oleic acid specifically induces the intermediate of apo-BLA at pH 4.0-4.5 to form insoluble amorphous aggregates.…”
Section: Discussionsupporting
confidence: 58%
“…H 1 ( d = 1) corresponds to the ChemBioDraw Ultra (Perkin Elmer, Waltham, Massachusetts, USA) simulation of oleic acid. H 2 corresponds to the Hamiltonian specified in reference . Scalar coupling values were: methyl–methylene, 8 Hz; methylene–methylene, 7.1 Hz; methylene–allylic, 7.1 Hz; three bond allylic–olefinic, 6.2 Hz; four bond allylic–olefinic, 1.75 Hz; olefinic–olefinic, 16 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The molten globule-like conformational states of -LA are not significantly populated at physiological conditions [26]. In addition, stable unfolded states of -LA only persist at low pH or in the absence of metal ions, since the protein instantly returns to the native conformation, if solution conditions are re-normalized [19].…”
Section: Folding Of α-Lamentioning
confidence: 97%
“…The binding of Ca 2+ to -LA through re-normalization of the solvent Ca 2+ , temperature or pH conditions, and the release of Ca 2+ through low pH, EDTA or heat treatment, have been shown in both circular dichroism spectroscopy and fluorescence spectroscopy data analysis, to cause structural and functional changes mainly in the tertiary structure, while leaving a native-like secondary structure [13,18,20,24,26]. The native folded Ca 2+ -bound -LA has higher structural stability against increased temperatures, pressures or denaturant concentrations [13,24,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%